Digital security in families: the sources of information relate to the active mediation of internet safety and parental internet skills. Issue 5 (4th April 2022) - Dedkova, Lenka; Smahel, David; Just, Mike
ABSTRACT: Home users of information and communication technologies are often the target of online attacks. At the same time they tend to lack the knowledge and skills to effectively protect themselves. Families with children are in a particularly difficult position since parents are responsible not only for their own digital safety, but of their children's too. This study focuses on the sources of digital security information used by parents. The aim of this study was to determine the factors that are associated with parents' preferences for digital security information. To achieve this aim, we conducted an online survey of 331 Czech parents and examined the patterns of sources used for digital security information using latent class analysis. This analysis identified four groups of parents: (1) those relying predominantly on the internet in general, (2) those using specialised sources (expert websites and professionals), (3) those utilising a wide spectrum of sources, including internet, television, and friends and family, and (4) those who predominantly gain information from their partners, and partially from specialists. The study also shows that the preferences of specific sources are connected to parental mediation practices and both parents' internet skills.